Understanding Identity Development as a Science Teacher Educator Through Shifts in Pedagogical Equilibrium - Mansfield, Jennifer; Park Rogers, Meredith; Berry, Amanda (Frontiers in Education, 2022)
This article reports research investigating the identity development of an experienced science teacher educator (Author 1) through the lens of pedagogical equilibrium. Despite previous experience as a secondary science teacher and science teacher educator, Author 1 found herself questioning her feelings of legitimacy and relevance when teaching pre-service primary science teachers. Identifying moments of disturbance in her pedagogical equilibrium, and working with a critical friend to analyse her ideas and experiences, she began to develop her professional self-understanding, contributing to improved feelings of credibility, and professional identity development. Emerging from this study, Author 1 experienced two important shifts in her perspective and understanding of her role. The first shift concerned recognising the different sources that comprised her ‘authority of experience’ as a science teacher educator, while the second shift involved learning to see pre-service teachers in her classes as future teachers, rather than ‘students’. These shifts in perspective were facilitated through applying self-study as the research methodology. The study provides insights into the identity formation processes of an early career teacher educator, as well as the value of pedagogical equilibrium and self-study for exploring teacher educator identity.